DISSOLUTION OF FLUORIDE IN GROUNDWATER: A WATER-ROCK INTERACTION STUDY - Saxena V.K.; Ahmed S. (My University, 2001)
Fluoride-rich groundwater is well known in granite aquifers in India and the world. Although its presence is necessary, chances of health risk become high if the fluoride concentration is more than the permissible limit of 1.5 mg/l (World Health Organization, WHO) in drinking water. Fluoride mainly occurs in groundwater as a natural constituent. Results of a laboratory study on water-rock interaction at normal temperature, pressure and different chemical conditions indicate that the specific conductivity, pH, Ca and HCO3 are important chemical parameters for the dissolution of fluoride to groundwater from fluoride-rich minerals (e.g., fluorite). Experimental results indicate that an alkaline medium (pH=7.6 to 8.6), high HCO3 concentration (ranging from 350-450 mg/l), and moderate specific conductivity (ranging from 750-1,750 S/cm) are favourable for fluoride dissolution. No significant correlation existed between fluoride and CaHCO3.
Keywords: Fluoride; Water-rock interaction; Granite rocks; Weathering; Dissolution